Clinical significance of pathologic abnormalities in biopsy samples from the appendiceal orifice. Issue 5 (6th August 2021) - Castrodad‐Rodríguez, Carlos A.; Choudhuri, Jui; El‐Jabbour, Tony; Cheng, Jerome; Westerhoff, Maria; Panarelli, Nicole C.
Abstract : Aims: Appendiceal orifice mucosa often appears inflamed endoscopically, even when other colonic segments appear normal. Histological findings in biopsy samples taken from endoscopically abnormal mucosa may simulate a variety of inflammatory colitides. We performed this study to evaluate the clinical implications of inflammatory changes isolated to the appendiceal orifice. Methods and results: In this double cohort study, biopsy samples from 26 histologically abnormal appendiceal orifices were reviewed. Twenty‐five control cases were culled from endoscopically normal ( n  = 11) and abnormal ( n  = 14) appendiceal orifices that were histologically normal. Histological findings were correlated with presentation, medication history, findings at other colonic sites and clinical outcomes. Study cases displayed active inflammation ( n  = 12), chronic active inflammation ( n  = 13) or features simulating collagenous colitis ( n  = 1). Eighteen patients had biopsies taken from other colonic sites; these revealed benign polyps ( n  = 10) or displayed active ( n  = 4) or chronic active ( n  = 4) inflammation. All patients with findings isolated to the appendiceal orifice were asymptomatic at most recent clinical follow‐up. Four of eight (50%) of the patients with inflammation in other biopsy samples were ultimately diagnosed with ulcerative colitis, in keeping with the well‐established role of the appendix as a 'skip lesion' in that disorder. Control patients presented for screening colonoscopy ( n  = 19), iron deficiency anaemia ( n  = 3) or change in bowel habits ( n  = 3) and none reported gastrointestinal symptoms upon follow‐up, regardless of the endoscopic appearance of the appendiceal orifice. Conclusion: Isolated inflammation of the appendiceal orifice mucosa should not be regarded as a feature of evolving inflammatory bowel disease or other types of chronic colitis. Abstract :